Pengaruh Content Creator Marketing Platform Instagram Terhadap Purchase Intention (Studi Kreator Konten Postingan Bengkulu Bikin Lapar) - Utama, Dion Alif (Managament Insight: Jurnal Ilmiah Manajemen, 2025)
In today's digital era, technology is developing rapidly so that digital developments also develop. With the internet, it is easier for all existing needs to be practical and efficient, including the need for business. Business in the digital era has undergone many changes, including in marketing. According to De Vries and Carlson (2014) continuing the theory from Gensler et al (2013), Presence on social networks has become an important part of marketing strategy: online product promotion through business accounts and advertising on social networking platforms have proven efficient. This study uses quantitative methods in which there is a variable hypothesis testing. In this study, data were collected through online questionnaires using a 5-point Likert scale, the data collection method was non-probability sampling with purposive sampling as a sampling method, and 190 respondents were obtained, data processing techniques used SPSS Statistical Package for Social Science version 21. The analytical method used is multiple linear regression analysis. The results of this study indicate that: 1) Content Creator variable has a positive effect on Purchase Intention, 2) Parasocial Interaction variable has a positive effect on Purchase Intention, 3) Credibility variable has a positive effect on Purchase Intention, and 4) Content Creator, Parasocial Interaction, and Credibility variables both have a positive effect on the Purchase Intention variable. Keyword: Parasocial Interaction; Credibility; Content Creator; Purchase Intention